Pelatihan Pembuatan Media Literasi Narasi dengan Teknik Parafrase Guru SD Negeri 10 Manurunge Kecamatan Tanete Riattang Kabupaten Bone - Rukayah; Sidrah Afriani Rahman; Asia M; Mujahidah; Muhammad Awal Nur (Jurusan Pendidikan Guru Sekolah Dasar Kampus VI Bone, 2026)
The aim of PKM activities is to increase knowledge and skills in designing literacy media and produce literacy media that can develop students' literacy skills in supporting literacy programs. The targets of the socialization were teachers at SD Negeri 10 Manurunge, Tenete Riattang District, Bone Regency. Teachers as the front guard have a key role in changing this situation through creative strategies, including providing literacy media that suits students' interests and conditions, not just students spending time reading without understanding the content they are reading. Implementation methods, starting from planning, implementation and evaluation. As a result of the activity, participants responded positively to this activity because they gained practical knowledge in developing their creativity and enriching the collection of materials in the reading corner in the classroom for each participant. Participants are expected to produce literacy media that can stimulate and develop students' interest in reading. In conclusion, this activity has given birth to a literacy media product using story paraphrasing techniques which can be used as literacy media (reading and writing) that supports student literacy culture programs in elementary schools, especially at SDN 10 Manurunge at all grade levels